The phenomenon of historical memory throughthe prism of disciplinary approaches - Zheshka, Yahor I. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
This article presents a classification of works devoted to the study of the phenomenon of historical memory. A systemic and comparative analysis of this phenomenon is conducted within the framework of social and humanitarian approaches. Key features of the areas related to these approaches are described. It is established that the sociological approach, due to its cognitive potential and the ability to obtain a representative empirical base, can serve as the core of an interdisciplinary strategy for the study of historical memory. A philosophical approach appears promising for studying new aspects of the phenomenon of historical memory in the absence of access to a large number of information sources. An anthropological approach allows us to establish a correspondence between the theses postulated by individuals about the content of their own historical memory and their manifestations in the everyday lives of informants. Political science and psychological approaches provide information on the phenomenon of historical memory from the perspective of aspects lying beyond the subject field of sociology (the legislatively enshrined position of government bodies regarding historical memory and its unconscious content). Historical, linguistic, and literary approaches allow us to turn to the study of additional sources, such as photographs, artifacts, and media materials. It is noted that the conclusions obtained using each of the approaches make a significant contribution to the understanding and interpretation of the phenomenon of historical memory in specific sociocultural conditions.
Keywords: historical memory; disciplinary approaches; social sciences and humanities